Punishment in times of conflict: justifications, rationales and effects - Noah Hefetz, R (2023)
Throughout the history of conflict, states have used various mechanisms to confine enemy fighters, including detention as Prisoners-of-War, administrative detention, and imprisonment as convicted offenders. This thesis studies incarceration in times of conflict as a form of punishment. It explores various forms of detention during hostilities and identifies common themes of unwarranted severity, deviation from basic criminal law principles and the targeting of minorities. The thesis proposes the term conflict penality to capture the special characteristics of how states punish perceived enemies. It develops the conceptual framework of conflict penality by examining the case study of Israel’s penal policies against Palestinian insurgents. It does so by discussing separately the approaches of the prisons, the political administration, and the Supreme Court of Israel. Exploring how different state actors engage with and justify special penal policies, the thesis provides a close analysis of how the Israeli-Palestinian conflict shaped Israel’s punishment of Palestinians, and vice versa, how state authorities use their penal power to better manage Israel’s interests in the ongoing conflict, in ways that exacerbate the political divide. The thesis develops several insights into how conflict reveals the politicisation of punishment, and how the framework of conflict penalty can improve our understanding of general criminal justice practices that operate in societies stratified by class and race tensions.